S142 Neutrophil lymphocyte ratio (NLR) as a predictive biomarker in idiopathic pulmonary fibrosis (IPF). (December 2018) - Mikolasch, TA; Sahota, J; Garthwaite, HS; Win, T; Ganeshan, B; Heightman, M; Hoy, L; Machado, M; Groves, AM; Porter, JC
Abstract : Introduction: IPF is a heterogeneous disease, and, due to the absence of predictive biomarkers, prognostic estimates rely on clinical scoring systems such as GAP (Gender, Age, Physiology). As GAP is relatively 'static', additional biomarkers are needed for more accurate prediction of disease progression and therapeutic response. Neutrophil: Lymphocyte ratio (NLR) has been shown to be of prognostic value in cancer and inflammatory pathologies but has never been investigated in IPF. Methods: The optimal NLR cut-off was determined in an unbiased fashion in a prospectively recruited training cohort of patients with IPF (n=75). This was validated in a second cohort of unselected IPF patients (n=143) from our clinical database. Confounding factors such as steroid therapy or haematological diseases were accounted for. Statistical analysis was performed in STATA 15. Results: The mortality of patients with a high NLR increased significantly compared to low NLR in single-variable Cox regression (Hazard Ratio (HR) 2.0, 95% CI 1.3 to 3.3, p=0.004) as well as in multi-variable regression adjusted for GAP stage (HR 2.1, 95% CI 1.3 to 3.6, p=0.003). NLR can be used to further stratify GAP stages (figure 1). Mean NLR fell with antifibrotic treatment in the high NLR group from baseline to 12 month follow-up but not in the low NLR group (p=0.04). There was no significant correlation between NLR category and GAP stage, FVC or TLCO at presentation. Steroid therapy of more than 5 mg of prednisolone was associated with high NLR category (p=0.009) but removing patients on steroid therapy did not alter NLR predictive power significantly (HR 2.3, 95% CI 1.3 to 4, p=0.005). A composite GAP/NLR risk score (GAP Plus) provides a slightly more precise mortality prediction model compared to GAP alone (HR 2.1 95% CI 1.6 to 2.7, p<0.000 vs HR 2.1 95% CI 1.5 to 3, p<0.000). Conclusion: NLR is a simple and readily available biomarker, which predicts mortality in IPF. It is independent of the GAP score and refines mortality predictions within GAP stages in IPF. NLR can be lowered by antifibrotic treatment. It is therefore a possibly modifiable biomarker that could be used to monitor early treatment response. We are currently investigating this hypothesis.